Human Requirements Validation for Complex Systems Design - Gregoriades, Andreas; Hadjicosti, Jack; Florides, Christos; Pamapaka, Maria (My University, 2015)
One of the most critical phases in complex systems design is the requirements engineering process. During this phase, system designers need to accurately elicit, model and validate the desired system based on user requirements. Smart driver assistive technologies (SDAT) belong to a class of complex systems that are used to alleviate accident risk by improving situation awareness, reducing driver workload or enhancing driver attentiveness. Such systems aim to draw drivers’ attention on critical information cues that improve decision making. Discovering the requirements for such systems necessitates a holistic approach that addresses not only functional and non-functional aspects but also the human requirements such as drivers’ situation awareness and workload. This work describes a simulation-based user requirements discovery method. It utilizes the benefits of a modular virtual reality simulator to model driving conditions to discover user needs that subsequently inform the design of prototype SDATs that exploit the augmented reality method. Herein, we illustrate the development of the simulator, the elicitation of user needs through an experiment and the prototype SDAT designs using UNITY game engine.
Keywords: Complex systems; Driving simulator; Human factors analysis; Requirements discovery